Os gestos das mãos e a referenciação: investigação de processos cognitivos na narrativa oral - Ana Cristina Carvalho Pereira (2010)
The aim of this research is to contribute to the study of language and cognition and the definition of embodiment by seeking a better understanding of how thought and language are fundamentally linked to bodily action. We share the view that the way we categorize theworld and reflect it on our speech production is the result of a complex task involving perception, negotiation, and several complex strategies, and that the linguistic structures are related and motivated by human knowledge, bodily experience and the communicative functions of discourse. Thus, considering that both speech and gesture are part of our communicative practice, we develop a psycholinguistic experiment to investigate the possibility of, in addition to the communicative function of hand gesture, their participation in the conceptualization, planning and organization of speech. Particularly emphasized were the referential process in oral production, such as the introduction and the co-referencing of lexical units and the management of the referential chain. The results were significant, as they showed a correlation between the strategies of referencing and different types of gestures asrevealed by different patterns of gestures occurrence in the different mechanisms present in the construction of the referential chain. It was also noticed a relationship between the specific difficulty level of the referential strategies and the occurrence of gestures.